Characterization of two novel variants of staphylococcal cassette chromosome mec elements in oxacillin-resistant Staphylococcus lugdunensis. (23rd August 2017) - Chang, Shih-Cheng; Lee, Ming-Hsun; Yeh, Chun-Fu; Liu, Tsui-Ping; Lin, Jung-Fu; Ho, Cheng-Mao; Lu, Jang-Jih
Abstract: Objectives: Staphylococcus lugdunensis, a species of CoNS, has become an important hospital pathogen because of increasing resistance to β-lactam antibiotics such as methicillin and oxacillin. Methicillin resistance is mainly due to the acquisition of the staphylococcal cassette chromosome (SCC) mec (SCC mec ). Little is known about the structure of SCC mec in methicillin- or oxacillin-resistant CoNS. Methods: WGS was performed to determine the structure of SCC mec elements of two clinical S. lugdunensis isolates: CMUH-22 and CMUH-25. Results: These elements were found to be flanked by DRs and IRs with unique mosaic structures and a common integration site in the 3′ end of the rlmH gene. The sequences of the regions located between rlmH and the ISSau4-like transposase genes of both elements were similar to those of SCC mec Vt of Staphylococcus aureus PM1. The SCC mec (type V, 5C2&4) of CMUH-25 harboured a novel ccrC complex and a C2-like mec complex in opposite orientations, similar to the type V SCC mec of S. aureus WIS. The sequences of the ccrA4B4 genes and J1 and J2 regions of CMUH-25 were similar to those of the SCC element of Staphylococcus haemolyticus NCTC 11042. In contrast, portions of the sequence of the J1 region of type Vt (5C2) SCC mec in strain CMUH-22 were highly similar to portions of those of Staphylococcus epidermidis RP62A and the composite SCC mec type V of S. aureus WAMRSA40. Conclusions: These observations suggest that the SCC mec elements of CMUH-25 and CMUH-22 evolved separately and assembled through different recombination events.